The Implementation Of Risk Management In The Ministry Of Energy And Mineral Resources' New Electricity Connection Assistance Program - Indira Cempakasari; Neneng Sri Rahayu; Luki Karunia (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
One of the government's programs aimed at improving access to electricity for the community to achieve a national electrification ratio of 100%, conducted by the Ministry of Energy and Mineral Resources, is the New Electricity Connection Assistance Program (NECAP). NECAP is a government initiative to equalize access to electricity throughout the archipelago to enhance electrification ratios and provide electricity to low-income households. NECAP covers the installation of electrical power, installation costs, Certification of Operation Eligibility (SLO) costs, new connection costs to PT PLN (Persero), and the initial purchase of electricity tokens. Risk management is required to identify and manage risks in order to achieve these objectives. The aim of this research is to provide an overview of the implementation of risk management in the NECAP program. The method used in this research is interviews with individuals directly involved in the NECAP program. The results of this research include a list of risks and how risk management is implemented in the NECAP program.